PENGARUH KAPITALISASI SAHAM TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Yenni Del Rosa, Yenni Del Rosa; Idward, Idward (MENARA EKONOMI, 2018)
This study aims to determine the effect of stock capitalization on Indonesia's economic growth. The type of secondary data research data obtained from the reseach library is quantitative data. All classical assumptions meet before the data is processed. Data analysis techniques using simple linear regression analysis at a significance level of 5% with the regression equation Y = 29.126 + 0.321X + e. The research hypothesis was accepted because 2,321> 1,667 or 0.003 <0.05. Stock capitalization correlation with Indonesia's economic growth is high (0.821) and the coefficient of determination 67.4% means that Indonesia's growth is affected by the share capitalization of 67.4% and the remaining 32.6% is influenced by other factors not included in the research model.